To be or not to be a cytochrome: electrical characterizations are inconsistent with Geobacter cytochrome ‘nanowires’ - Guberman-Pfeffer, Matthew J. (Frontiers in Microbiology, 2024)
Geobacter sulfurreducens profoundly shapes Earth's biogeochemistry by discharging respiratory electrons to minerals and other microbes through filaments of a two-decades-long debated identity. Cryogenic electron microscopy has revealed filaments of redox-active cytochromes, but the same filaments have exhibited hallmarks of organic metal-like conductivity under cytochrome denaturing/inhibiting conditions. Prior structure-based calculations and kinetic analyses on multi-heme proteins are synthesized herein to propose that a minimum of ~7 cytochrome 'nanowires' can carry the respiratory flux of a Geobacter cell, which is known to express somewhat more (≥20) filaments to increase the likelihood of productive contacts. By contrast, prior electrical and spectroscopic structural characterizations are argued to be physiologically irrelevant or physically implausible for the known cytochrome filaments because of experimental artifacts and sample impurities. This perspective clarifies our mechanistic understanding of physiological metal-microbe interactions and advances synthetic biology efforts to optimize those interactions for bioremediation and energy or chemical production.